2009
DOI: 10.1007/s00417-009-1090-x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic monitoring of occlusion treatment for amblyopia in patients aged 7 to 16 years

Abstract: This study presents for the first time objective treatment and dose response data in amblyopic patients beyond the "classical" treatment age. Electronic monitoring of occlusion and considerable amounts of patching were shown to be feasible. The acuity results indicate that there is a potential for improvement, yet treatment seemed to be less efficient than shown by previous studies in younger patients. Continuation of this research may advance the discussion about age-dependent evidence-based amblyopia treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
33
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 30 publications
2
33
0
5
Order By: Relevance
“…The authors presented well, for the first time, objective treatment and dose-response data in amblyopic patients beyond the "classical" treatment age, and demonstrated that it was practical to apply electronic monitoring of occlusion therapy in amblyopic patients [1].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors presented well, for the first time, objective treatment and dose-response data in amblyopic patients beyond the "classical" treatment age, and demonstrated that it was practical to apply electronic monitoring of occlusion therapy in amblyopic patients [1].…”
mentioning
confidence: 99%
“…Thus, data loss due to dropout of patients from the study or due to ODM loss or failure, battery and storing capacity exhaustion was minimized [1]. In term of mechanism, the ODM measures temperature difference between the surface of the eye and the surroundings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor, Thank you for forwarding the letter by Garebaghi et al regarding our article "Electronic monitoring of occlusion treatment for amblyopia in patients aged 7 to 16 years", published in Graefe's Archive in 2009 [1]. We presented there data of a special group-patients beyond the classical age for amblyopia treatment-collected with the Occlusion Dose Monitor developed in The Netherlands [2,3].…”
mentioning
confidence: 92%
“…klusionszeiten weniger belastend, je jün-ger das Kind ist [3]. So kann in den ersten Lebensjahren, in denen die Plastizität und Lernfähigkeit des Sehsystems am höchs-ten ist (.…”
unclassified